Pengaruh Cash Flow dan NPM terhadap Stock Price (Studi Empiris pada Perusahaan LQ 45 di BEI) - Derdjo Djony Saputro; Sri Astuti (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2018)
The purpose of this study is to examine whether the stock price can be influenced by cash flow and net profit margin. This study uses the LQ 45 company listed on the Indonesia Stock Exchange as a research population. The data used are secondary data available in the Financial Statements of LQ 45 companies in the period 2013 - 2017. The population contained in this study are 45 companies, then produced a sample of 41 companies through sampling techniques using purposive sampling method. Hypothesis testing is done by using multiple linear regression analysis techniques with SPSS version 20 application tools. The results of this study indicate that cash flow has a positive and significant effect on the stock price, and the net profit margin has a negative and insignificant effect on the stock price of the listed LQ 45 companies. on the Indonesia Stock Exchange.